Analisis Penyederhanaan Struktur Organisasi Perangkat Daerah Kabupaten Pemalang - Kristiana Lina Dewi; Hardi Warsono; Budi Puspo Priyadi; Retno Sunu Astuti; Teuku Afrizal (Universitas Medan Area, 2022)
The simplification of the organizational structure does not change the typology of regional apparatus but simplifies the organizational structure into two levels. The simplification of the structure does not remove the duties of the functions of government affairs but shifts the executor of the functions into functional officials with certain expertise and skills. The purpose of this simplification of the organizational structure is to make the government administration system more effective and efficient. While this article aims to determine the analysis of the simplification of the bureaucratic structure in Pemalang Regency. This study uses a qualitative approach. The theory that researchers use in this study is the theory of organizational restructuring. The research method is done by document study, observation, and interviews. The results of the study indicate that the simplification of the organizational structure in Pemalang Regency needs to be a common concern.